Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
Both are true.
Step-by-step explanation:
If f(x) = 2x³ + 6
To find the inverse of the given function,
Rewrite the function in the form of an equation,
y = 2x³ + 6
Interchange the variables x and y,
x = 2y³ + 6
Solve for y,
2y³ = x - 6
y = [tex]\sqrt[3]{\frac{(x-6)}{2}}[/tex]
Rewrite the equation in the form of a function,
[tex]f^{-1}(x)={\sqrt[3]{\frac{(x-6)}{2}}[/tex]
[tex](fof^{-1})(x)=f[f^{-1}(x)][/tex]
= [tex]2(\sqrt[3]{\frac{(x-6)}{2}})^3+6[/tex]
= (x - 6) + 6
= x
[tex](f^{-1}of)(x)=f^{-1}[{f(x)][/tex]
[tex]={\sqrt[3]{\frac{(2x^3+6-6)}{2}}[/tex]
[tex]={\sqrt[3]{\frac{(2x^3)}{2}}[/tex]
= x
Therefore, both the statements are true.
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.